LINC00941 affects the proliferation, apoptosis and differentiation of osteoblasts by regulating the miR-335-5p/KAT7 axis - Longjin Liu; Ye Yang; Pengxiao Sun (Journal of Orthopaedic Surgery and Research)
Abstract Background Fractures are the prevalent traumatic conditions encountered in orthopedic practices. The rising incidence of fractures has emerged as a pressing global health concern. Although the majority of individuals with fractures experience complete recovery of bone structure and function, approximately 10% of those with fractures exhibit delayed fracture healing (DFH). The objective of this investigation was to explore the function and underlying mechanisms of LINC00941 in the advancement of DFH, as well as its involvement in the regulation of osteoblastic differentiation by regulating the miR-335-5p/KAT7 axis. Methods The expression levels of LINC00941, miR-335-5p, KAT7 and osteoblast differentiation-related markers were assessed using RT-qPCR. The proliferation of MC3T3-E1 cells was evaluated through the CCK-8 assay, and cell apoptosis was analyzed via flow cytometry. The targeted regulatory relationships between LINC00941 and miR-335-5p, as well as between miR-335-5p and KAT7 were verified by a dual-luciferase reporter gene assay. Result The expression of LINC00941 was significantly up regulated, while miR-335-5p exhibited a notable downregulation in DFH patients, both of LINC00941 and miR-335-5p have been identified as potential predicted markers for DFH. Furthermore, LINC00941 has been demonstrated to inhibit osteoblast proliferation, promote apoptosis, and suppress osteoblast differentiation through the regulation of the miR-335-5p/KAT7 axis. Conclusion LINC00941/ miR-335-5p/KAT7 axis may be a therapeutic target for DFH.